Viruses that affect Argentinian honey bees (Apis mellifera) - Salina, Marcos Daniel (2021)
Beekeeping is a widespread activity in Argentina, mainly producing honey that has gained both national and international recognition. There are more than 3,000,000 hives in the country, mainly concentrated in Buenos Aires Province (approximately 1,000,000 hives). In recent decades, worrying rates of hive loss have been observed in many countries around the world. In Latin America, the estimated loss of hives is between 13% (Peru and Ecuador) and 53% (Chile). Argentina had annual losses of 34% for the period of October 1, 2016 to October 1, 2017. The causes of these losses are not clear but probably involve multiple stressors that can act simultaneously. One of the main causes of loss of bee colonies worldwide is infestation by the ectoparasitic mite Varroa destructor in combination with viral infections. To date, 10 viruses have been detected that affect honey bees (Apis mellifera) in Argentina. Of these, deformed wing virus, sacbrood virus, acute bee paralysis virus, chronic bee paralysis virus, and Israeli acute bee paralysis can be transmitted by mites. Deformed wing virus and the AIK complex are the viruses most often associated with loss of hives worldwide. Considering that bee viruses have been detected in Argentina in several hymenopteran and non-hymenopteran insects, these hosts could act as important natural reservoirs for viruses and play an important role in their dispersal in the environment. Further studies to investigate the different mechanisms by which viruses spread in the environment will enable us to develop various strategies for the control of infected colonies and the spread of viruses in the habitat where they are found.